1
$\begingroup$

$f(Θ)$ is pdf of gamma distribution

$$f(Θ) = \frac{λ^α}{Γ(α)}Θ^{α-1}\exp(-λΘ), $$

$$X\mid Θ \sim \mathrm{poisson}(Θ) \rightarrow \frac{Θ^x\exp(-Θ)}{x!}$$

Suppose that $Θ$ is a random variable that follows a gamma distribution with parameters $λ$ and $α$, where $α$ is an integer, and suppose that, conditional on $Θ$, $X$ follows a Poisson distribution with parameter $Θ$. Find the unconditional distribution of $α + X$ (Hint : Find the mgf by using iterated conditional expectations.

please answer..

$\endgroup$
  • $\begingroup$ I don't know what the notation $\displaystyle gx\mid\Theta(x) = \cdots$ means. I'm guessing you meant the conditional distribution, given $\Theta$, of $X$, is a Poisson distribution with expected value $\Theta$. One could write $X\mid\Theta \sim \mathrm{Poisson}(\Theta)$. At any rate, one should not use the same symbol, in this case $\Theta$, to refer both to a random variable and to the argument to the density function. One can write $f_\Theta(\theta)=\text{a function of }\theta$. That is fairly standard. Distinguishing, for example, between $Y$ and $y$ makes it possible to${}\,\dots$ $\endgroup$ – Michael Hardy Oct 18 '15 at 4:21
  • $\begingroup$ $\ldots\,{}$to understand something like $\Pr(Y\le y)$. ${}\qquad{}$ $\endgroup$ – Michael Hardy Oct 18 '15 at 4:21
1
$\begingroup$

I will distinguish between $\Theta$ and $\theta$ as described in the comments. We have \begin{align} & \Pr(X=x) = \operatorname{E}(\Pr(X=x\mid\Theta)) = \operatorname{E}\left( \frac{\theta^x e^{-\theta}}{x!} \right) = \int_0^\infty \frac{\theta^x e^{-\theta}}{x!} f_\Theta(\theta)\,d\theta \\[10pt] = {} & \frac 1 {x!} \int_0^\infty \theta^x e^{-\theta} \frac{\lambda^\alpha}{\Gamma(\alpha)}\theta^{\alpha-1}e^{-\lambda\theta} \, d\theta = \frac {\lambda^\alpha} {x!\Gamma(\alpha)} \int_0^\infty \theta^{x+\alpha-1} e^{-\theta(1+\lambda)} \, d\theta \end{align}

The substitution $\eta = \theta(1+\lambda),\quad$ $\dfrac{d\eta}{1+\lambda} = d\theta$ then gets you some constant times a value of the Gamma function.

You will need to know why $\dfrac{\Gamma(x+\alpha)}{\Gamma(\alpha)} = \alpha(\alpha+1)(\alpha+2)\cdots(\alpha+x-1)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.